Effects of different nodulation varieties and row spacings on nodule growth, dry matter accumulation and distribution of relay strip intercropping soybean - PANG Ting; SHUAI Peng; CHEN Ping; DU Qing; FU Zhidan; YANG Wenyu; YONG Taiwen (浙江大学学报. 农业与生命科学版)
Soybean is an important grain and oil crop in China. However, with the decrease of economic benefits and cultivated area, it depends on imports heavily due to the unbalanced supply and demand. Intercropping systems are widely used because they can increase crop yield, nutrient use efficiency, and land productivity. In particular, legume/crop intercropping systems can increase nitrogen fixation, reduce nitrogen input, enhance nitrogen use efficiency, and thereby increase crop yield. Maize/soybean relay strip intercropping system is the major planting pattern in the southwest of China, which can increase soybean yield and land output. The objective of this study is to investigate the effects of different interspecific spacings of maize/soybean intercropping on biomass, dry matter allocation and yield of soybean with different nodulation characteristics, and make a progress for the research of yield and nutrient utilization in maize/soybean relay strip intercropping system.To explore the effects of soybean varieties and row spacings on soybean nodule growth, biomass accumulation and distribution, we carried out a field experiment with two- factor randomized block design, and applied three kinds of row spacing between maize and soybean (B1: 45 cm, marked as IS45; B2: 60 cm, marked as IS60; B3: 75 cm, marked as IS75) and two soybean varieties (A1: weak-nodulation Gongxuan No. 1, A2: strong-nodulation Nandou No. 25).The results revealed that the effects of shade on soybean decreased with the increase of row spacing between maize and soybean. With the increase of row spacing, the nodule number and dry mass of soybean increased from the third trifoliolate stage to full bloom stage of soybean. The soybean nodule number and dry mass reached its maximum at beginning seed stage, with the following order: IS60>IS75>IS45. Compared with A1, the nodule number was lower and the nodule dry mass was greater in A2. From the third trifoliolate stage to full bloom stage, shoot dry matter accumulation declined with the decrease of row spacing and mainly distributed to stems and leaves; in addition, the dry matter accumulation of stems, leaves and shoots was lower in A2 in comparison with A1. From beginning seed stage to full maturity stage, the shoot dry matter increased rapidly, but the allocated rate of stems and leaves decreased; however, the allocated rate of pods increased and reached its peak at full maturity stage and B2 treatment. The output rate and contribution rate of vegetative organ for A2 were greater in contrast with A1, and the grain yield of A2 was 2.94% higher than that of A1. In addition, under different row spacing treatments, the grain yield of B2 was 9.77% and 2.67% higher than that of B1 and B3, respectively.In sum, the yield of soybean reaches the maximum under the 60 cm row spacing. In contrast to weak-nodulation soybean cultivar, the grain yield increase of strong-nodulation soybean can be responsible for the increase of pod per plant and 100-grain mass.